2021
DOI: 10.21203/rs.3.rs-365252/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative and bioinformatics integrated strategy to investigate the pharmacological mechanism of Ermiao Wan against eczema

Abstract: BackgroundErmiao Wan (EMW) is used to treat eczema in China. However, its underlying pharmacological mechanisms against eczema remain unclear. MethodsIn this study, the components of EMW were quantitatively analyzed using HPLC. The role of the components, targets, and signaling pathways were predicted by network pharmacology. Moreover, molecular docking was used to verify the binding forces of the components with the target proteins. ResultsThe results showed that the established HPLC method is simple and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The top genes involved in these signaling pathways were AKT1, JNK, and JUN (Figure 4b), suggesting that AKT1, JNK, and JUN play a key role in the process of COVID‐19. Some studies have suggested that JNK may be a target for some traditional Chinese medicine to improve COVID‐19 (Hao et al, 2020; Huang, Bai, et al, 2020; Huang, Zheng, et al, 2020; Xia et al, 2021). JUN (v‐jun avian sarcona virus 17 oncogene homolog) plays an important role in controlling malignant transformation of cells (Kappelmann, Bosserhoff, & Kuphal, 2014; Kumar & Sharma, 2021), though its role in COVID‐19 is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The top genes involved in these signaling pathways were AKT1, JNK, and JUN (Figure 4b), suggesting that AKT1, JNK, and JUN play a key role in the process of COVID‐19. Some studies have suggested that JNK may be a target for some traditional Chinese medicine to improve COVID‐19 (Hao et al, 2020; Huang, Bai, et al, 2020; Huang, Zheng, et al, 2020; Xia et al, 2021). JUN (v‐jun avian sarcona virus 17 oncogene homolog) plays an important role in controlling malignant transformation of cells (Kappelmann, Bosserhoff, & Kuphal, 2014; Kumar & Sharma, 2021), though its role in COVID‐19 is unclear.…”
Section: Discussionmentioning
confidence: 99%